2009
DOI: 10.1111/j.1365-2052.2008.01815.x
|View full text |Cite
|
Sign up to set email alerts
|

A genome map of divergent artificial selection between Bos taurus dairy cattle and Bos taurus beef cattle

Abstract: A number of cattle breeds have become highly specialized for milk or beef production, following strong artificial selection for these traits. In this paper, we compare allele frequencies from 9323 single nucleotide polymorphism (SNP) markers genotyped in dairy and beef cattle breeds averaged in sliding windows across the genome, with the aim of identifying divergently selected regions of the genome between the production types. The value of the method for identifying selection signatures was validated by four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
113
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 29 publications
7
113
2
Order By: Relevance
“…Changes in the genomes of different breeds of domesticated pigs detected by comparing SNP allele frequencies with those of ancestral wild boars are attributed to nearby genes under selection (Ai et al., 2015; Li et al., 2013). Similar studies have been published in cattle (Hayes et al., 2008; The Bovine HapMap Consortium 2009) and sheep (Chessa et al., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Changes in the genomes of different breeds of domesticated pigs detected by comparing SNP allele frequencies with those of ancestral wild boars are attributed to nearby genes under selection (Ai et al., 2015; Li et al., 2013). Similar studies have been published in cattle (Hayes et al., 2008; The Bovine HapMap Consortium 2009) and sheep (Chessa et al., 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified high levels of between-breed genetic differentiation near coat colour loci, including MC1R (see §2a) and the Charolais dilution factor (Dc locus), indicating that these genes have been important in the establishment of cattle breeds [26,27]. Another gene that has been implicated as a possible target of selection based on allele-frequency differences between cattle breeds is the growth hormone receptor (GHR) gene [26][27][28].…”
Section: Selective Forcesmentioning
confidence: 99%
“…It has become crucial in biomedical sciences, where it can help to identify genes related to disease resistance (Tishkoff et al 2001;Barreiro et al 2008;Albrechtsen et al 2010;Fumagalli et al 2010;Cagliani et al 2011), adaptation to climate (Lao et al 2007;Sturm 2009;Rees and Harding 2012), or altitude (Bigham et al 2010;Simonson et al 2010). In livestock species, where artificial selection has been carried out by humans since domestication, it contributes to map traits of agronomical interest, for instance, related to milk (Hayes et al 2009) or meat (Kijas et al 2012) production.Efficiency of methods for detecting selection varies with the considered selection timescale (Sabeti et al 2006). For the detection of selection within species (the ecological scale of time), methods can be classified into three groups: methods based on (i) the high frequency of derived alleles and other consequences of hitchhiking within population (Kim and Stephan 2002;Kim and Nielsen 2004;Nielsen et al 2005;Boitard et al 2009), (ii) the length and structure of haplotypes, measured by extended haplotype homozygosity (EHH) or EHH-derived statistics (Sabeti et al 2002;Voight et al 2006), and (iii) the genetic differentiation between populations, measured by F ST or related statistics (Lewontin and Krakauer 1973;Beaumont and Balding 2004;Foll and Gaggiotti 2008;Riebler et al 2008;Gautier et al 2009;Bonhomme et al 2010).…”
mentioning
confidence: 99%
“…It has become crucial in biomedical sciences, where it can help to identify genes related to disease resistance (Tishkoff et al 2001;Barreiro et al 2008;Albrechtsen et al 2010;Fumagalli et al 2010;Cagliani et al 2011), adaptation to climate (Lao et al 2007;Sturm 2009;Rees and Harding 2012), or altitude (Bigham et al 2010;Simonson et al 2010). In livestock species, where artificial selection has been carried out by humans since domestication, it contributes to map traits of agronomical interest, for instance, related to milk (Hayes et al 2009) or meat (Kijas et al 2012) production.…”
mentioning
confidence: 99%